2007
DOI: 10.3892/ijo.30.4.865
|View full text |Cite
|
Sign up to set email alerts
|

Ephrin-A1 is a negative regulator in glioma through down-reguation of EphA2 and FAK

Abstract: Eph receptors, the largest receptor tyrosine kinases, and their ephrin ligands play important roles in axon guidance and cell migration during development of the nervous system. Recently, these molecules are also found involved in tumorigenesis of different kinds of cancers. In this study, we demonstrated that expression of ephrin-A1 was dramatically downregulated in glioma cell lines and in primary gliomas compared to the matched normal tissues. Forced expression of ephrin-A1 attenuated cell migration, cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 28 publications
3
42
0
Order By: Relevance
“…These results demonstrated that EphA2 signaling through FAK can promote cellular adhesion and invasion. Similar results were recently reported by Liu and colleagues, who observed that forced expression of ephrin-A1 in glioma cell lines resulted in the degradation of EphA2 concomitant with a downregulation of FAK resulting in an inhibition of cellular migration, proliferation, and anchorage independent growth (Liu et al, 2007). Collectively, these studies suggest that signaling through EphA2 and ephrin-A1 can result in either promotion or inhibition of cellular adhesion, migration, and invasion depending on the cell type.…”
Section: Focal Adhesion Kinase Signaling As a Mediator Of Melanoma Vmsupporting
confidence: 76%
“…These results demonstrated that EphA2 signaling through FAK can promote cellular adhesion and invasion. Similar results were recently reported by Liu and colleagues, who observed that forced expression of ephrin-A1 in glioma cell lines resulted in the degradation of EphA2 concomitant with a downregulation of FAK resulting in an inhibition of cellular migration, proliferation, and anchorage independent growth (Liu et al, 2007). Collectively, these studies suggest that signaling through EphA2 and ephrin-A1 can result in either promotion or inhibition of cellular adhesion, migration, and invasion depending on the cell type.…”
Section: Focal Adhesion Kinase Signaling As a Mediator Of Melanoma Vmsupporting
confidence: 76%
“…63 On the other hand, eprhin-A1 down-regulates FAK In human glioma U251 cells. 64 Our present and previous results demonstrate that FAK protein levels can be both down-regulated (by motility) and up-regulated (by exposure to TGF-␤) in intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 88%
“…This receptor-ligand system is involved in a variety of biological events (Poliakov et al, 2004;Huberman et al, 2005;Kuijper et al, 2007). Although a majority of investigators have studied the role of Eph/ ephrin in development, emerging evidence suggests strong involvement in tumorigenesis, including metastasis, invasion, and angiogenesis (Surawska et al, 2004;BrantleySieders et al, 2006;Liu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%